Posted by **sydney** on Thursday, December 21, 2006 at 2:50am.

how do i change x^2-4x-32=0 into (x+4)(x-8)=0

x^2-4x-32=0

=> x^2-8x+4x-32=0

=> x(x-8)+4(x-8)=0

=> (x-8)(x+4)=0

OR (x+4)(x-8)=0

X

^{2} -4x -32 = 0

JUst factor it. It factors into

(X-8)(X+4)=0

## Answer this Question

## Related Questions

- Derivatives - What is the fourth derivative of f(x)= e^-x^2. I got f''(x)=-2e^-x...
- Powers in Math - (5a^3b^4)^2=? *I don't get this one...PLease Help! (5a3b4)2= (5...
- Chemistry - Sorry for posting this again, I dont know if the question was ...
- Calc, Implicit Differentiation - Regard y as independent variable and x as ...
- math2 - 5y^8-125 *you have to factor completley easy. Take out the five: 5(y^8-...
- math-volume - I'm confused with how to solve this problem, so help would be ...
- help - Y^3Y/Y^-2 If you post with the correct word in the Subject line, you'll ...
- Property of logarithms - Using property of logarithms, how do I prove derivative...
- Maths/Right Triangle - There must be a relationship (formula) between the ...
- algebra - How do you factor 4x(squared)+12x+40? Thanks! 4x2+12x+40= 4(x2+3x+10) ...

More Related Questions